Navigating Moral Dilemmas: Teaching Ethics and Citizenship in Delta State’s Higher Education Institutions (HEIs) - Juliet Nkonyeasua Ossai; Rhoda Nkemdilim Eboh (Social Empowerment Journal, 2025)
This study examined the various strategies for navigating ethical and moral dilemmas in social studies through the teaching of responsible citizenship in higher education institutions (HEIs) in Delta State, Nigeria. It employed descriptive survey. The population consisted of 828 management staff and Social Studies lecturers in higher education institutions (HEIs) in Delta State. A sample of 394 management staff and Social Studies lecturers combined was chosen using stratified random sampling technique from the higher education institutions in Delta state comprising universities, and colleges of education. It utilized a structured questionnaire using four-point Likert scale which was validated by three experts from Faculty of Education, Delta State University, Abraka and had a reliability of 0.82, while z-test statistics was used to test the hypotheses at 0.05 level of significance. The findings revealed that: the managerial strategies of implementation of school policies enhanced academic achievement of undergraduates and promotes responsible citizenship consciousness amongst staff and students. The strategies employed include safeguarding and utilizing social studies teaching and learning facilities efficiently, anticipation of any innovation that can aid the effective teaching and learning of responsible citizenship, develop efficient social studies school programmes, engage staff and students in discussions on responsible citizenship to clear the ethical and moral dilemmas. Based on the findings, the researcher recommends among others that regular in-service training on school management should be arranged for management staff, Social Studies lecturers and students by the government through the schools’ management in collaboration with the Delta State Ministry of Education.